University dropout intention: analysis during covid-19 - Olmedo-Cifuentes, Isabel; Martínez-León, Inocencia Mª (Journal of Management and Business Education, 2022)
Dropout intention is critical information for universities to help them avoid the misuse of financial, social, and personal resources. COVID-19 has forced universities to adapt their face-to-face teaching-learning processes to distance education, something neither they nor their students were prepared for. Despite being digital natives, students are not used to the online teaching-learning model that has been imposed. Therefore, knowing the effects of this situation on significant variables for universities and students, such as university experience, motivation, satisfaction, and commitment, can help universities understand why students drop out. This preliminary empirical research with university students has three objectives. First, we ascertain students’ perceptions about the possible causes of dropout intention after the outbreak of COVID-19. Second, we determine other variables affecting intentions to drop out, such as university experience, academic motivation, academic satisfaction, satisfaction with blended and distance education, and student commitment. Third, we examine whether these variables affect dropout intention in an exploratory way. Through an online questionnaire, 191 responses from university students were obtained at a Spanish public university. Empirical analyses identify little practical training, teaching methods that fail to motivate students, the absence of commitment to students on the part of the university, and a lack of information and support from the university as the main reasons students consider dropping out. These results are the same in the general sample and in the sub-sample of those who seriously considered leaving university. For the last group, other causes could be considered, such as students’ emotions, assessment systems, and relationships with teachers. All the mean assessments of the variables used in this study are medium-low. Academic motivation is the best-valued (3.38 out of 5), whereas satisfaction with blended and distance education is the worst (2.31 out of 5). Dropout intention is estimated at 2.56 out of 5. Although this is not a low result, this and the rest of the results may have been affected by the pandemic. Additionally, the study justifies that the better the university experience, academic motivation, general academic satisfaction, and satisfaction with blended and distance education, the lower the dropout intention rate. Surprisingly, student commitment does not influence students’ decisions to leave university. The main contribution of this study is to offer guidelines to reduce dropout intention. Training courses for students and teachers seem to be the best way to reduce dropout rates, but other aspects, such as university experience, motivation, and satisfaction, which help to maintain student expectations even in difficult situations, are also important. Although more research is needed, the proposed model offers the possibility of applying and comparing it with other Spanish and European universities, or even high schools, with students who are about to graduate and enter university.